Green Innovation, CSR, and Governance: Driving Sustainable Corporate Value Creation - Yenny Wati; Yusrizal Yusrizal; Helly Aroza Siregar; Suhardjo Suhardjo; Nicholas Renaldo (Jurnal Akuntansi Keuangan dan Bisnis, 2025)
This research seeks to explore the impact of green innovation and green corporate social responsibility (green CSR) on corporate value, with green governance serving as a moderating variable. The study employs a quantitative methodology utilizing secondary data from companies listed on the Indonesia Stock Exchange (IDX) that were involved in the PROPER assessment from 2020 to 2024. The analysis is conducted using a moderation regression test facilitated by SPSS software. The results show that green innovation and green CSR greatly improve corporate value. Additionally, green governance has been shown to enhance the link between green innovation, green CSR, and corporate value. This indicates that the extent to which green innovation and green CSR boost corporate value is heavily influenced by the green governance practices adopted. This research reinforces stakeholder theory, legitimacy theory, and signaling theory in the context of corporate sustainability. For policymakers, these results emphasize the need for rules and rewards that enhance green governance as a key driver for effective corporate sustainability strategies. The originality of this research lies in including the green governance moderating factor in the model that links green innovation, green CSR, and corporate value, which has not been widely studied in emerging markets.